Aggregation-induced emission active luminescent polymeric nanoparticles: Non-covalent fabrication methodologies and biomedical applications. (December 2017) - Wan, Qing; Huang, Qiang; Liu, Meiying; Xu, Dazhuang; Huang, Hongye; Zhang, Xiaoyong; Wei, Yen
Graphical abstract: Recent developments and progress on the non-covalent fabrication and biomedical applications of luminescent polymeric nanoparticles with aggregation-induced emission feature were summarized in the review article. Highlights: Aggregation-induced emission active materials. Non-covalent fabrication of AIE-active luminescent polymeric nanoparticles. Biological imaging of AIE-active luminescent polymeric nanoparticles. Therapeutic applications of AIE-active luminescent polymeric nanoparticles. Abstract: Aggregation-induced emission (AIE) phenomenon was first reported by Tang et al. in 2001. Since then, the AIE-active functional materials have attracted more and more attention for different applications. Especially, the fabrication and biomedical applications of AIE-active polymeric probes have been the research frontiers in chemistry and materials fields recently. Great achievements and advances have been made in the fabrication and biomedical applications of AIE-active polymers. More and more attention has been paid to the fabrication of AIE-active polymers through non-covalent methods, although these AIE-active polymers from non-covalent strategies are expected to possess unique features (e.g. responsiveness and biodegradability). In this review, the recent developments in the non-covalent fabrication of AIE-active luminescent polymeric nanoparticles (LPNs) and the potential biomedical applications of these AIE-active LPNs are summarized. A number of fabrication strategies based on non-covalent methods such as encapsulation by amphiphilic copolymers, supramolecular inclusion, Schiff base and phenyl borate and electrostatic interaction are included. The potential biomedical applications included biological imaging, and theranostics based on these AIE-active LPNs were also highlighted. Finally, the issues and future direction about AIE-active LPNs were also pointed out in the end. We trust this review will inspire great research interest from scientists from different research fields in chemistry, materials, biology and interdisciplinary areas and significantly promote the development of AIE-active polymers for biomedical applications.